Bandgap, electrical and structural properties of thick InN (0001) films grown under optimal conditions. (May 2019) - Adikimenakis, A.; Androulidaki, M.; Foundoulaki Salhin, E.; Tsagaraki, K.; Doundoulakis, G.; Kuzmik, J.; Georgakilas, A.
Abstract: The improvement potential for the structural, electrical and opto-electronic properties of heteroepitaxial InN-on-GaN (0001) films by using optimal conditions (substrate temperature, In and N fluxes) of plasma-assisted molecular beam epitaxy and increasing the epilayer thickness to few micrometres has been investigated. The increase of InN thickness to 3.7 μm resulted to a-type component threading dislocation density of 6x10 9 cm −2 and directly measured electron mobility of 2330 cm 2 /Vs and concentration of 4.5x10 17 cm −3 . The optical bandgap of this film at 300K was 0.637 eV. However, a degradation in the integrity of the interfacial InN/GaN region was observed in films thicker than 1 μm, with the formation of voids and the nucleation of microcracks, which may be related to strain relaxation or thermal decomposition.